Risk Communication and Miscommunication : Case Studies in Science, Technology, Engineering, Government, and Community Organizations - Boiarsky, Carolyn R. (Book collections on Project MUSE., 2016)
"Boiarsky draws from research in rhetoric, linguistics, technical communication, and psychology for a new approach at risk communication and the communication skills necessary for dealing with environmental and technological problems that could lead to major crises "--